Bibliometric analysis on carcinogenic and non-carcinogenic risk assessment of heavy metals from cereal products - Gabriel Mustatea; Andreea L. Mocanu; Corina A. Stroe; Laurentiu Berca; Elena L. Ungureanu (Exploration of Foods and Foodomics)
Heavy metal contamination of food is a critical global health issue due to its toxic, bioaccumulative, and often carcinogenic effects. This study presents a comprehensive bibliometric analysis of research published between 2000 and 2024 on health risk assessments associated with heavy metal exposure through the consumption of cereal products. Data were extracted from the Web of Science database and analyzed using VOSviewer software to visualize trends in terms of authors, institutional and international collaboration, and areas of thematic interest. The findings reveal a growing scientific interest in this field, with a peak in publication volume in 2020. China emerged as the main contributor, accounting for almost half of all publications, followed by Iran, Spain, and Brazil. The Chinese Academy of Sciences and Shahid Beheshti University of Medical Sciences were among the most active institutions. Journals such as Environmental Science and Pollution Research and Science of the Total Environment were identified as key publication platforms. The collaborative analysis highlights China and the USA as major centres of international collaboration, with peripheral but active contributions from countries such as England, Bangladesh, and Malaysia. Most studies focused on exposure pathways and assessed both carcinogenic and non-carcinogenic health risks, frequently reporting values above safe thresholds. These findings highlight the urgent need for national long-term monitoring programmes and the development of country-specific strategies to reduce exposure to heavy metals in food, thereby enhancing public health protection and regulatory compliance.